2010
DOI: 10.1039/b925250a
|View full text |Cite
|
Sign up to set email alerts
|

MALDI-TOF mass spectrometry speciation of staphylococci and their discrimination from micrococci isolated from indoor air of schoolrooms

Abstract: The focus of our work is the identification of medically relevant staphylococci from the environment; these organisms are among the major opportunistic pathogens associated with human disease. Andersen sampling was performed in schoolrooms during the school year. Eleven of thirty six isolates (all Gram-positive tetrads) were identified as staphylococci and 23 were characterized as micrococci. MALDI-TOF MS profiling was used as the first stage in the classification followed by standard biochemical tests includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…Investigators have previously noted the significant content of desquamated human skin cells in aerosols in occupied settings and the presence of bacteria including Staphylococcus , Propionibacteria , Corynebacteria , and enteric bacteria, which are typically ascribed to human microflora [30,31]. A survey in three university laboratories in Italy discovered that the most frequently observed bacteria were Staphylococcus , Bacillus , and Actinomyces [32]. The fungi most commonly found indoors were Alternaria spp., Aspergillus spp., and Cladosporium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators have previously noted the significant content of desquamated human skin cells in aerosols in occupied settings and the presence of bacteria including Staphylococcus , Propionibacteria , Corynebacteria , and enteric bacteria, which are typically ascribed to human microflora [30,31]. A survey in three university laboratories in Italy discovered that the most frequently observed bacteria were Staphylococcus , Bacillus , and Actinomyces [32]. The fungi most commonly found indoors were Alternaria spp., Aspergillus spp., and Cladosporium spp.…”
Section: Discussionmentioning
confidence: 99%
“…are able to be reliably identified by using the BioTyper software. In a study of environmental micrococci, isolates were identified correctly to the genus level, but no species-level identification could be reached due to limited entries in the database (94). It is likely that with the appropriate database, specieslevel discriminations could be made when necessary.…”
Section: Micrococcimentioning
confidence: 99%
“…In these cases, ITR-PCR can be used to identify rare phenotypes and aberrant species. Although ITR-PCR has some limitations in the identification of certain closely related species (Fox et al, 2010), the S. saprophyticus isolates exhibited a unique band pattern. In addition, other species which are difficult to differentiate from S. saprophyticus by ITR-PCR, such as Staphylococcus chromogenes, Staphylococcus cohnii, Staphylococcus equorum, Staphylococcus gallinarum, Staphylococcus lentus, and Staphylococcus xylosus (Couto et al, 2001), were not detected in this study and are usually not associated with UTI in humans.…”
Section: Discussionmentioning
confidence: 99%